2014
DOI: 10.3171/2014.2.focus13559
|View full text |Cite
|
Sign up to set email alerts
|

Odilon Marc Lannelongue (1840–1911) and strip craniectomy for craniosynostosis

Abstract: In the 19th century, Dr. Odilon Marc Lannelongue was a pioneering French surgeon who introduced a surgical technique for the treatment of craniosynostosis. In 1890, Dr. Lannelongue performed correction of sagittal synostosis by strip craniectomy. From his procedure, multiple techniques have been developed and endorsed for this condition, ranging from simple suturectomies to extensive calvarial vault remodeling. In addition, even today, endoscopically aided strip craniectomy is performed as a surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Originally, the fused suture was released by making strip craniotomy lines on both sides of the suture. Later strip craniectomy of the ossified suture itself was performed 3,4 . Currently more extensive calvarial vault reconstructions are preferred 5,6 or endoscopic strip craniectomies are done followed by postoperative molding therapy with helmets 3,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, the fused suture was released by making strip craniotomy lines on both sides of the suture. Later strip craniectomy of the ossified suture itself was performed 3,4 . Currently more extensive calvarial vault reconstructions are preferred 5,6 or endoscopic strip craniectomies are done followed by postoperative molding therapy with helmets 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently more extensive calvarial vault reconstructions are preferred 5,6 or endoscopic strip craniectomies are done followed by postoperative molding therapy with helmets 3,7 . At [BLINDED] the early operative method included two parallel strip craniotomies lateral to the midline, while a strip of bone was left over the sagittal sinus according to Lannelongue 4 . Later additional silicone membranes were used on the craniotomy lines 8 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for craniosynostosis include extensive surgical procedures such as total cranial vault remodeling [5] and strip craniectomy [6], or less invasive endoscopic approaches [7]. In 1998, a new technique for treating scaphocephaly was first reported by Lauritzen et al with the use of spring devices [8].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1840, Bir et al reported some mental retardation secondary to the microcephaly of craniosynostosis. Further, Bir et al determined that excision of the fused sutures could prevent later intellectual impairment (22). Single suture craniosynostosis suffices for the development of raised ICP; neurodevelopmental delay in single suture craniosynostosis patients can be as high as 37%.…”
Section: Craniosynostosismentioning
confidence: 99%